NSUN4-mediated m5C RNA methylation protects retinal cells against excitotoxic injury via the SHH signaling pathway - Yahong Li; Dian Li; Chao Geng; Ruihua Wei; Yajian Duan (PLoS ONE, 2026)
Glaucoma, a leading global cause of blindness, is characterized by progressive retinal neuronal loss. NOP2/Sun RNA methyltransferase 4 (NSUN4), a writer of 5-methylcytosine (m5C) RNA modifications, has established roles in methylation and mitoribosome assembly, yet its function in retinal cell survival remains unexplored. In this study, integrated methylated RNA immunoprecipitation sequencing (MeRIP-seq) and RNA-seq analysis in an NMDA-induced retinal injury model revealed widespread mRNA hypomethylation enriched in the Sonic Hedgehog (SHH) signaling pathway, accompanied by significant downregulation of Nsun4 . To investigate the underlying mechanisms, we utilized the R28 retinal cell line, a widely accepted model for studying retinal neuroprotection. In glutamate-stimulated R28 cells, NSUN4 overexpression mitigated excitotoxic injury, attenuating Ca² ⁺ overload, mitochondrial dysfunction, and apoptosis. Mechanistically, NSUN4 enhanced m5C methylation on key SHH pathway transcripts ( Shh, Gli1, and Gli2 ). Crucially, the neuroprotective effect of NSUN4 was abolished upon pharmacological inhibition of the SHH pathway using Vismodegib, confirming that pathway activation is essential for NSUN4-mediated protection. Clinically, NSUN4 levels were significantly reduced in the aqueous humor of patients with primary open-angle glaucoma compared to controls. Together, these findings establish NSUN4 as an m5C-dependent activator of the SHH pathway that protects retinal cells against excitotoxic injury, nominating it as a novel candidate for glaucoma neuroprotection.